2002
DOI: 10.1590/s1415-65552002000200003
|View full text |Cite
|
Sign up to set email alerts
|

Conselhos de administração: análise de sua composição em um conjunto de companhias abertas brasileiras

Abstract: RESUMOO presente trabalho visa a identificar o perfil dos conselhos de administração de 142 companhias brasileiras listadas na Bolsa de São Paulo, a partir de dados do encerramento do exercício de 1999. Os conselheiros foram divididos em quatro categorias distintas, cujos critérios de separação seguiram a metodologia adotada por Bhagat e Black (2000). Foi avaliado o grau de independência do conselho de administração em relação aos acionistas controladores. Foram ainda realizadas análises para identificar carac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
16

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 8 publications
1
11
0
16
Order By: Relevance
“…Punsuvo et al (2007) and Oliveira et al (2012). This finding is also in line with Dutra and Saito (2002) who had already revealed the scarce use of cumulative voting in the country. between CG practices and activism.…”
Section: Activism Indexsupporting
confidence: 87%
See 1 more Smart Citation
“…Punsuvo et al (2007) and Oliveira et al (2012). This finding is also in line with Dutra and Saito (2002) who had already revealed the scarce use of cumulative voting in the country. between CG practices and activism.…”
Section: Activism Indexsupporting
confidence: 87%
“…This evidence appears to contradict Strickland, Wiles and Zenner's (1996) suggestion that activism is lower when there are many small shareholders, given their lack of motivation for engaging in activist initiatives. However, as observed by Dutra and Saito (2002), this can be explained in the case of Brazil by the high degree of control rights concentration, which, in many cases, prevents minority shareholders from jointly attaining the minimum percentage necessary to request the adoption of cumulative voting.…”
Section: Activism Indexmentioning
confidence: 99%
“…Administrators will have great leeway in setting their own compensation, with the associated risks, if this happens. Dutra and Saito (2002), for instance, concluded that minority shareholders rarely used the cumulative voting right, which would more easily allow the election of their representatives to the BOD (Lei n. 6404, art. 141).…”
Section: Literature Reviewmentioning
confidence: 99%
“…O conselho de administração surge em um contexto também em que empresas não possuem administradores externos trabalhando em prol dos interesses dos acionistas, deste modo, uma alternativa é a criação do conselho de administração. No Brasil em específico este organismo encontra-se principalmente em empresas com capital aberto, integrado por profissionais eleitos pelos acionistas, com o intuito de primarem pelos interesses destes (DUTRA; SAITO, 2002).…”
Section: Características Do Conselho De Administraçãounclassified
“…Para Cheng (2008) o tamanho do conselho de administração pode facilitar o cumprimento das atribuições deste, sendo que quanto maior, mais este consegue influenciar as operações e decisões das empresas, reportando em políticas e divulgações mais concisas perante os usuários externos. Também, de acordo com autores (BEASLEY, 1996;DUTRA;SAITO, 2002;COLES;DANIEL;NAVEEN, 2008;BEBCHUK;WEISBACH, 2010) quanto mais independentes forem os conselheiros, mais estes terão neutralidade em suas ações, executando as funções críticas para o acompanhamento e aconselhamento da gestão.…”
Section: Características Do Conselho De Administraçãounclassified